Pro ASP.NET 1.1 in VB .NET: From Professional to Expert - Moroney, Laurence (Apress, 2012)
ASP.NET is Microsoft’s next-generation technology for creating server-side web applications. It’s built on the Microsoft .NET Framework, which is a cluster of closely related new technologies that revolutionizes everything from database access to distributed applications. ASP.NET is one of the most important components of the .NET Framework—it’s the part that enables you to develop high-performance web applications and web services. The traditional concepts involved in creating web applications still hold true in the .NET world. Each web application is made up of web pages. You can render rich HTML and even use JavaScript, create components that encapsulate programming logic, and tweak and tune your applications using configuration settings. However, behind the scenes ASP.NET works quite differently from traditional scripting technologies like classic ASP (Active Service Pages) or PHP (PHP: Hypertext Preprocessor). It’s also much more ambitious than JSP (Java Server Pages).